Health, sleep and lack of time: relations to domestic and paid work in nurses Saúde, sono e falta de tempo: relações com o trabalho profissional e doméstico em enfermeiras - Luciana Fernandes Portela; Lúcia Rotenberg; William Waissmann (Universidade de São Paulo, 2005)
OBJECTIVE: To assess whether reported morbidity and complaints of lack of time and sleep are associated with the burden of professional work and housework among nurses. METHODS: A cross-sectional exploratory study was carried out among female nurses and nurse assistants (N=206) of a public hospital in Rio de Janeiro, Brazil. Data were collected by means of a questionnaire. The prevalence ratio and 95% confidence intervals were estimated. RESULTS: Mean duration of professional work and housework time was 40.4 and 31.6 hours/week, respectively. Long professional working time (over 44 hours/week) were associated with mild emotional disorders (PR=1.37; 95% CI: 1.05-1.80), complaints of lack of time for resting/leisure (PR=1.61; 95% CI: 1.31-1.97), housework (PR=1.48; 95% CI: 1.12-1.97), and childcare (PR=1.99; 95% CI: 1.51-2.63). Long housework time (over 28 hours/week) was associated with lower prevalence of lack of time for childcare (PR=0.62; 95% CI: 0.46-0.84). High housework load was associated with lack of personal time and complaints of varicose veins (PR=1.31; 95% CI: 1.14-1.50 and PR=1.31; 95% CI: 1.08-1.58, respectively). Complaints of varicose veins were also frequent among female nurses with a total work load above 84 hours (PR=1.30; 95% CI: 1.05-1.61), though this group has shown a lower prevalence of arterial hypertension and recurrent headaches (PR=0.35; 95% CI: 0.15-0.83 and PR=0.53; 95% CI: 0.32-0.89, respectively). CONCLUSIONS: Results suggest that both professional and home environments are relevant in the evaluation of work overload on nurses' health and their family and social life. It is stressed the need for instruments for analyzing total workload among female populations. OBJETIVO: Avaliar a associação entre a carga de trabalho profissional e doméstico com doenças e queixas sobre o sono e falta de tempo em enfermeiras. MÉTODOS: Estudo exploratório transversal com profissionais de enfermagem do sexo feminino (N=206) de um hospital público no Rio de Janeiro, Brasil. Os dados foram obtidos por meio de questionário. Foram estimadas as razões de prevalência e seus intervalos de confiança de 95%. RESULTADOS: A duração média das jornadas semanais profissional e doméstica foram de 40,4h e 31,6h, respectivamente. Jornadas profissionais longas (acima de 44h) se associaram ao relato de tensão, ansiedade ou insônia (RP=1,37;IC 95%: 1,05-1,80), à falta de tempo para o descanso/lazer (RP=1,61; IC 95%: 1,31-1,97), o cuidado da casa (RP=1,48; IC 95%: 1,12-1,97) e dos filhos (RP=1,99; IC 95%: 1,51-2,63). Jornadas domésticas longas (acima de 28h) se associaram à menor prevalência de queixas de falta de tempo para os filhos (RP=0,62; IC 95%: 0,46-0,84). A alta sobrecarga doméstica relacionou-se à falta de tempo para si e ao relato de varizes (RP=1,31; IC 95%: 1,14-1,50 e RP=1,31; IC 95%: 1,08-1,58, respectivamente). Este último também foi mais freqüente entre aquelas cuja carga total de trabalho excedeu 84h (RP=1,30; IC 95%: 1,05-1,61), embora tenham apresentado menor prevalência do relato de hipertensão arterial e de dor de cabeça freqüente (RP=0,35; IC 95%: 0,15-0,83 e RP=0,53; IC 95%: 0,32-0,89, respectivamente). CONCLUSÕES: Os resultados sugerem que há que se valorizar tanto a esfera profissional quanto a doméstica na avaliação da sobrecarga de trabalho sobre a saúde e a vida socio-familiar de enfermeiras. Ressalta-se a demanda por instrumentos de análise que levem em conta as cargas laborais totais que se impõem sobre populações femininas.